Pengaruh Dana Pihak Ketiga dan Car Terhadap Pembiayaan Mudharabah Dengan NPF Sebagai Variabel Moderating Pada Bank Umum Syariah di Indonesia - Ahmad Irsan; Irfan; Widia Astuty (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
The purpose of this study was to examine and analyze the effect of third party funds (DPK) and Capital Adequacy Ratio (CAR) on mudharabah financing at Sharia Commercial Banks in Indonesia. To test and analyze whether Non-Performing Financing (NPF) can moderate the effect of third party funds (DPK) and Capital Adequacy Ratio (CAR) on mudharabah financing at Sharia Commercial Banks in Indonesia. This research uses an associative quantitative approach method with data collection techniques through documentation study. with secondary data. The population of this research is Sharia Commercial Bank Companies in Indonesia which are registered with the Financial Services Authority (OJK). Samples were taken as many as 9 Islamic Commercial Banks. The observation year started from 2015-2019. The data collection technique was using purposive sampling. This research is a statistical analysis method using the SEM Partial Least Square (PLS) model. The results of this study indicate that the variable third party funds have an effect on mudharabah financing at Indonesian Sharia Commercial Banks. CAR does not affect mudharabah financing at Indonesian Islamic Commercial Banks. n that NPF cannot moderate third party funds against mudharabah financing at Indonesian Sharia Commercial Banks. NPF also cannot moderate CAR towards mudharabah financing at Indonesian Sharia Commercial Banks.